Enhanced microwave heat susceptor crucible / Muhammad Azwadi Sulaiman ... [et al.] - Sulaiman, Assoc. Prof. Dr. Muhammad Azwadi; Mohd Pabli, Fathin Asila; Muhamad Sharifuddin, Syifa'; Mohamed, Assoc. Prof. Dr. Julie Juliewatty; Ibrahim, Dr. Norfadhilah (2021)
Microwave (MW) irradiation is an attractive technique of material processing. Reasons for the growing interest in the use of microwave energy are including rapid heating, enhanced densification rate, decreased sintering active energy and improved microstructure. MW heating also has the potential for energy and cost savings when comparing with conventional heating. The use of microwave in ceramic processing is a relatively recent development. The technique can be applied effectively and efficiently to heat and sinter ceramic object. In this study, the microwave heat susceptor crucible was formulated and enhanced to convert the microwave energy to heat at very high efficiency. The performance was surpassing the existing product in market and the invention was patented for commercialization.